Development Of Efficiency Enhancement For Renewable Energy Generation Using Supercapacitors - Roni Afrizal; Beni Satria; Solly Aryza (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
The increase in global energy demand drives the development of more efficient and environmentally friendly renewable energy sources. However, renewable energy generators, such as solar and wind power, face challenges in the form of output fluctuations that cause power instability. One solution that can be applied is the use of supercapacitors as energy storage to improve system efficiency and stability. This study aims to analyze the effect of supercapacitors on the efficiency of renewable energy generators by designing a supercapacitor-based energy storage system integrated with a voltage equalization system using MOSFETs. The methods used include design, simulation, and system testing to measure energy storage efficiency and voltage stability. The results of the study show that the integration of supercapacitors in renewable energy storage systems can increase system efficiency by up to 15% compared to systems without supercapacitors. In addition, the use of MOSFETs with low on-resistance can reduce power losses in the voltage equalization process. Thus, the use of supercapacitors in renewable energy storage systems has proven effective in improving the efficiency and stability of energy generators, as well as optimizing the use of renewable energy in meeting future energy needs.